Enantioselective Michael Addition of a Malonic Ester to a Maleic Ester Catalyzed by Lithium Binaphtholate - Sakamoto, Midori; Kaneko, Tetsuya; Orito, Yuya; Nakajima, Makoto (Synlett, 2016)
Lithium 3,3′-chlorobinaphtholate was found to catalyze the enantioselective Michael addition of a malonic ester to a maleic ester. High enantioselectivities (>90% ee) were observed, especially in the reactions of 2-alkylmalonic esters and maleic esters.
Keywords: asymmetric catalyst; asymmetric synthesis; enantioselectivity; Michael addition; chiral catalyst; lithium binaphtholate